The Historical Treatment of Urban Policing in Canada: A Review of the Literature - Ross, Jeffrey (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1995)
The author reviews the research produced on the history of municipal policing in Canada, partly through the creation and analysis of a database. There are three types of work: comprehensive treatments, historical case-studies of particular polic forces, and studies examining subprocesses in particular forces. The author then discusses this literature's advantages and disadvantages. Finally, the author makes a series of recommendations for improving the existing knowledge base.